1991
DOI: 10.3161/00159301ff1991.35.14.203
|View full text |Cite
|
Sign up to set email alerts
|

The influence of urbanization on the earthworm infection by monocystid gregarines

Abstract: Key words: earthw orm s, m onocystid gregarines, Apicom plexa, in fection, parasites, heavy m etals, u rbanization, Warsaw. i n t r o d u c t i o nA m odern c ity possessing vast green areas is generally stated to be an ecosystem in w h ich the basic elements o f its s tru c tu re and p rin cip le s of fu n c tio n in g are s im ila r to those o f n a tu ra l ecosystems ( P i s a r s k i and T r o j a n , 1 9 7 6 ; G e p p , 1 9 7 7 ) .The u rb a n iz a tio n o f an area involves m a n y serious im pacts on b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, there have been few reports of investigations of the impact of immunosuppression on the ability of the earthworm to respond to fungal, nematode or microbial attack. Pizl (1985) reported that earthworms from triazine-herbicide treated orchards were infected with moncystid gregarine parasites. Further laboratory studies confirmed that treatment with the herbicide increased the susceptibility of earthworms to infection by the parasites (Pizl 1985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few reports of investigations of the impact of immunosuppression on the ability of the earthworm to respond to fungal, nematode or microbial attack. Pizl (1985) reported that earthworms from triazine-herbicide treated orchards were infected with moncystid gregarine parasites. Further laboratory studies confirmed that treatment with the herbicide increased the susceptibility of earthworms to infection by the parasites (Pizl 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Pizl (1985) reported that earthworms from triazine-herbicide treated orchards were infected with moncystid gregarine parasites. Further laboratory studies confirmed that treatment with the herbicide increased the susceptibility of earthworms to infection by the parasites (Pizl 1985). Immunosuppression may also reflect the ability of the organism to withstand further environmental stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Epigeic earthworms were not detected in 34–38% of fields. Epigeic earthworms are tillage sensitive, and the most sensitive of the ecological groups to drought (Edwards & Bohlen, 1996) and are the most sensitive to parasitic infections in pesticide‐treated soils (Pizl, 1985). The lack of detection could be patchy distribution patterns associated with a dependence on surface litter conditions, tillage, environmental (earthworms losing too much water to survive a drought) or related to annelid disease (reducing resilience to environmental stresses); the latter is unknown because earthworms die and rapidly decay in their burrows creating a survivorship bias.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply positive impacts of human activities on local apicomplexan biodiversity, in line with a recent study showing that apicomplexan taxon richness was positively affected by urbanization degree to a larger extent compared to the metazoan counterpart 54 . Some studies stated that human activities and associated environmental changes, such as the application of herbicides 55 , heavy metal pollution 56 and SO2 deposition 57 , increased the infection of soil metazoa by eukaryotic unicellular parasites. However, the underlying mechanisms are still unknown.…”
Section: Discussionmentioning
confidence: 99%